Vulnerability to addiction. (15th March 2021) - Maldonado, R.; Calvé, P.; García-Blanco, A.; Domingo-Rodriguez, L.; Senabre, E.; Martín-García, E.
Abstract: Addiction is a chronic brain disease that has dramatic health and socioeconomic consequences worldwide. Multiple approaches have been used for decades to clarify the neurobiological basis of this disease and to identify novel potential treatments. This review summarizes the main brain networks involved in the vulnerability to addiction and specific innovative technological approaches to investigate these neural circuits. First, the evolution of the definition of addiction across the Diagnostic and Statistical Manual of Mental Disorders (DSM) is revised. We next discuss several innovative experimental techniques that, combined with behavioral approaches, have allowed recent critical advances in understanding the neural circuits involved in addiction, including DREADDs, calcium imaging, and electrophysiology. All these techniques have been used to investigate specific neural circuits involved in vulnerability to addiction and have been extremely useful to clarify the neurobiological basis of each specific component of the addictive process. These novel tools targeting specific brain regions are of great interest to further understand the different aspects of this complex disease. This article is part of the special issue on 'Vulnerabilities to Substance Abuse.'. Graphical abstract: Image 1 Highlights: Addiction is a chronic relapsing disorder characterized by the loss of inhibitory control despite adverse consequences. The individual vulnerability to addiction is a crucial component in the development of the pathology. Drug-taking initiation does not necessarily lead to addiction, and not all drug users become addicted. The behavioral animal model of addiction incorporates the main hallmarks that characterized this disease in human patients. Compulsivity is related to the connectivity strength of the medial PFC glutamatergic projections to the NAc.